Kathleen's story - McDaniel, Lurlene (New York : Delacorte Press, 2004)
With the support of her two best friends, sixteen-year-old Kathleen tries to balance her summer volunteer work at the hospital with her responsibilities caring for her mother, who has multiple sclerosis, and her attraction to a handsome boy.
Accelerated Reader AR
Keywords: Family problems -- Fiction; Interpersonal relations -- Fiction; Medical fiction; Multiple sclerosis -- Fiction; Mothers and daughters -- Fiction; Friendship -- Fiction; Christian life -- Fiction; Florida -- Fiction